Examining gender inequalities in Denmark: traveling concepts, intersectionality, and social democracy - Flaherty, Colm; Petersen, Katrine Ploug (Frontiers in Political Science, 2025)
Although Denmark is often regarded as a forerunner in terms of gender equality, Denmark still has no dedicated gender studies departments. Departing from this puzzling fact, this article asks how researchers working in Denmark understand, analyze, and investigate gender and gender structures in Denmark. We conduct a hermeneutic literature review, focusing on research produced between 2008–2023, and demonstrate that most research analyzing gender in Denmark belongs to four broad theoretical categories organized around institutional theories, citizenship theories, interactionism, and masculinities. Furthermore, we find some evidence that the absence of gender studies departments in Denmark contributes to an ongoing separation between political science and sociological research investigating similar topics. However, we show that the traveling concept of intersectionality unites research analyzing gendered inequalities in Denmark but note that authors seldom understand or use intersectionality in the same way. The article concludes by arguing that although the use of intersectionality has enriched research examining gender in Denmark, enabling research to illuminate different inequalities, research must also better account for the specificities of the Danish welfare state to understand the operation of power and continuing gender inequality in Denmark.